Design of a wideband 377 σ E-shaped patch antenna for rf energy harvesting - Devi, K. K. A.; Sadasivam, S.; Md. Din, Norashidah; Chakrabarthy, C. K.; Rajib, S. K. (Wiley Online Library, 2012)
The design of a 377 X E-shaped patch antenna with partial ground plane is presented and discussed in this article. Two parallel slots are introduced into the conventional patch antenna, and it was investigated by the currents through the patch to enhance its bandwidth. The antenna is designed, fabricated, and measured for downlink frequency band of GSM 900, which shows an impedance bandwidth of 29.03% (277 MHz) at 954 MHz.